Challenges for teaching in the area of production and operations in Colombia - Ocampo Flórez & Otro, Juan & Otro (Universidad Santo Tomás, Bogotá-Colombia, 2016)
Several authors have exalted the importance of teaching profile against the effectivenessof the teaching-learning process and proper development of skills instudents. Aware of this reality the high education institutions have undertaken acareer in order to identify elements that influence in the teaching and impact positivelyor negatively on skills training for students. For some authors, the domainof knowledge is supported by the teacher’s skills put into play in the exercise oftheirs formation´s task, which is achieved by training or professional experiencethat he possesses. With these elements often it built the appropriate profile foreach area of knowledge within the course curriculum.It addition to this, studies on trends for the skills required by the administrator, requiresa professional with capacity for take decision in under horizons of uncertainty,optimizing resources and the preservation and conservation of the environment,which is developed in the courses are classified in the area of Production andOperations. However, business schools in the country haven´t taken the step thatallows them to appropriate this trend, hence the low incidence of subjects and thelack of teacher guides that profile in the area.The purpose of these lines is to identify the relevance of the training of teachers of subjectsin the area of Production and Operations Management programs of the Facultiesof Business Administration affiliated chapter of ASCOLFA profile Bogotá, to proposeactions to strengthen one of the areas of greatest potential for management training.